Implementasi Peraturan Daerah Kota Pekanbaru Nomor 05 Tahun 2005 Tentang Pengawasan Dan Retribusi Pemeriksaan Kualitas Air (Studi Kasus Di Kecamatan Bukit Raya) - Triono, Joni; Rauf, Rahyunir (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2015)
This study aims to Know Implementation Regional Regulation No. 05 Year 2005 Pekanbaru About Supervision and Inspection Levy Water Quality Case Study dikecamatan Bukit Raya. This study uses quantitative methods with reference to the concept of George C. Edward III in 2009 stated Nugroho approaches used to study the implementation of policies that of Communication, Resources, Disposition, and Bureaucratic Structure. Implementation of these regulations allow an open and transparent approach so that all the processes involved in the process palaksanan local regulations can understand and can work didalamnya.yang become informants in this study is Chief Medical Officer of Pekanbaru, Field Control Health Problems, Head of Environmental Health Section , laboratory UPTD Pekanbaru City Health Department and the owner Depot Water Available dikecamatan Bukit Raya. In the method of data collection used questionnaires, interviews and documentation after collected were analyzed using descriptive analysis of quantitative and qualitative. The results of this study found that the implementation of Regulation No. 05 pekanbaru city area in 2005 on the supervision and examination charges and water quality dikecamatan highway hill by each indicator say enough good research. Based on this it is recommended should the City Health Office Pekanbaru perperan order to further enhance socialization and supervision based on the existing rules, and have sufficient personnel so that the purpose of the establishment of the city area pekanbaru No. 05 of 2005 on the supervision and inspection levy can water kwalitas is reached.